2020
DOI: 10.13141/jve.vol12.no2.pp70-77
|View full text |Cite
|
Sign up to set email alerts
|

Determining the content of toxic elements (Pb, Cd, and As) in herbal plants collected from different sites in northern Vietnam

Abstract: Plants might contain heavy metals from the surrounding polluted environment. Medicinal herb and plants, commonly used in Vietnam, may pose a risk to public health when polluted with heavy metals such as Pb, Cd and As. This study aims to investigate the content of Pb, Cd, and As in five selected herb plants (Phyllanthus urinaria L., Plantago asiatica L., Eleusine indica L., Wedelia chinensis (Osbeck) Merr, and Artemisia vulgaris L.). The samples were collected from natural sites in some pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…These four plants are common urban weeds in China, and plants of the same families span a wide geographic range across global urban spaces. In addition, they possess significantly different morphological and physiological traits (Table S2 and Figure S2A–J) and have demonstrated superenrichment of heavy metals in previous studies. The experiments were conducted in five replicates in a greenhouse (25 °C, 14 h light). Plants were collected from the campus of Chongqing University (Shapingba District, Chongqing, China), and no source of industrial pollution (e.g., factories) within 10 km was confirmed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These four plants are common urban weeds in China, and plants of the same families span a wide geographic range across global urban spaces. In addition, they possess significantly different morphological and physiological traits (Table S2 and Figure S2A–J) and have demonstrated superenrichment of heavy metals in previous studies. The experiments were conducted in five replicates in a greenhouse (25 °C, 14 h light). Plants were collected from the campus of Chongqing University (Shapingba District, Chongqing, China), and no source of industrial pollution (e.g., factories) within 10 km was confirmed.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, they have been shown to have promising applications in urban restoration practices. In fact, many of them can grow well under postmining site conditions, and they can serve as a good option in urban greening initiatives within polluted areas to develop species-rich plant communities and accumulate heavy metal pollutants. …”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in India reported As concentrations ranging from 0.16 to 1.1 mg kg −1 in medicinal plants [31] . Similarly, in a study conducted by Vuong et al [32] , mean As concentrations of 0.343 mg kg −1 , 1.628 mg kg −1 , 0.182 mg kg −1 and 0.295 mg kg −1 in Artemisia vulgaris L., Plantago asiatica L., Eleusine indica (L.) and Phyllanthus urinaria L., respectively [26] , [27] , [28] , [29] , [32] .
Fig.
…”
Section: Resultsmentioning
confidence: 67%
“…Another study in Nigeria reported a mean Cd concentration of 0.16 mg kg −1 in Moringa oleifera and 0.44 mg kg −1 in Azadirachta indica ) [46] , which are considerably higher compared to the findings in this study. In comparison to other medicinal herbs, a study conducted by Dghaim et al [47] reported mean Cd concentration ranging from 0.03 to 0.43 mg kg −1 (mean: 0.14 mg kg −1 ) in medicinal herbs commonly consumed in the United Arab Emirates while Sepehri et al [48] found Cd concentrations ranging from 0.012 mg kg −1 to 0.0793 mg kg − 1 in medicinal plants consumed in Iran indicating that Cd concentrations in Malawian medicinal herbs are significantly lower than those reported in medicinal plants from other regions [12] , [32] , [49] , [50] , [51] , [52] .…”
Section: Resultsmentioning
confidence: 99%
“…Data analysis showed a significant differences between means at (P=.0001) using SPSS statistic version 25 software and One-way ANOVA test Consumption of spicy and medical plants are widely distributed. However, in addition to organic material, plants can also contain heavy metals from the surrounding polluted environment (Truong., 2020), and accumulate different element with concentration higher than its content in the environment and up to 20 000 times (Ref). Fluoride content in different sources was widely investigated using different detection methods.…”
Section: Determination Of Fluoride In Rosemary Samplesmentioning
confidence: 99%